Welche Anforderungen stellen Pflegeheime an ein elektronisches Pflegedokumentationssystem? Eine Analyse mit Fokus auf die Demenz. - Imhof, Stefan; Händler-Schuster, Daniela; Angerer, Alfred (Pflegewissenschaft, 2021)
The main objective of the study is to determine functional requirements for an electronic nursing documentation system (NDS) using dementia care as an example. Furthermore, mobile NDS are also considered. The study design consists of methods of qualitative research combined with design thinking. Interviews with eleven stakeholders in Swiss nursing homes resulted in an overview of 127 functions that a NDS should cover. These include resident specific functions, functions of the care process and overarching functions. Moreover, the study revealed an interaction diagram that identifies the most important processes and stakeholders in the context of NDS.